Intrinsic and extrinsic motivation in youths: a comparison between recreational and competitive athletes - Ye, P.; Shi, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this study was to explore whether intrinsic and extrinsic motivational differences existed amongst recreational and competitive athletes. Methods The Sport Motivation Scale (SMS, Pelletier et al., 1995) was administered to 113 recreational athletes and 102 university athletes aged from 18 to 25 years old (M=20.7). The recreational athletes had participated in sports for five years on average. The SMS measures 3 types of Intrinsic Motivation (IM; IM to Know, IM to Accomplish Things, and IM to Experience Stimulation), and 3 types of Extrinsic Motivation (External Regulation, Introjection, and Identification), and motivation. Results / Discussion A 2 (athletes) x 2 (gender) analysis of variance (ANOVA) showed significant main effects for athletes on External Regulation, Introjection, Identification, IM-to Know, and IM-Accomplish Things. No significant main effects of gender were found on all SMS subscales. The findings revealed that competitive athletes had higher levels of sport motivation than recreational athletes overall Consistent with earlier research (Fortier et al., 1995), the results revealed that recreational athletes had a lower level of identification than competitive athletes. Furthermore, extrinsic motivation (External Regulation and Introjection) in recreational athletes were found to be less than in competitive athletes, suggesting that competitive athletes were more extrinsically motivated than recreational athletes. The results demonstrated that competitive athletes had higher levels of IM-to Know and IM-to Accomplish Things than recreational athletes, and no difference in A motivation in contrast with, previous research (Fortier et al., 1995) which indicated that recreational athletes had higher levels of IM-to Accomplish Things and IM-to Experience Stimulation, and Amotivation than competitive athletes.